(untitled) (XXI Century. Spanish Literature and Culture, 2014)
A difficult and unconventional relationship with simbolism. A constant search between Ethics and Aesthetics, between thought and emotion. Tecnicly a sort of collage. A minimal contribution to the effort we, the woman, make with the aim of transforming a Cultura and with this Culture her arguments and believes that have ignored always our efforts.